Knowledge of obstetric danger signs and birth preparedness practices among women in rural Uganda - Kabakyenga Jerome K; Östergren Per-Olof; Turyakira Eleanor; Pettersson Karen O (BMC, 2011)
Abstract Background Improving knowledge of obstetric danger signs and promoting birth preparedness practices are strategies aimed at enhancing utilization of skilled care in low-income countries. The aim of the study was to explore the association between knowledge of obstetric danger signs and birth preparedness among recently delivered women in south-western Uganda. Methods The study included 764 recently delivered women from 112 villages in Mbarara district. Community survey methods were used and 764 recently delivered women from 112 villages in Mbarara district were included in study. Interviewer administered questionnaire were used to collect data. Logistic regression analyses were conducted to explore the relationship between knowledge of key danger signs and birth preparedness. Results Fifty two percent of women knew at least one key danger sign during pregnancy, 72% during delivery and 72% during postpartum. Only 19% had knowledge of 3 or more key danger signs during the three periods. Of the four birth preparedness practices; 91% had saved money, 71% had bought birth materials, 61% identified a health professional and 61% identified means of transport. Overall 35% of the respondents were birth prepared. The relationship between knowledge of at least one key danger sign during pregnancy or during postpartum and birth preparedness showed statistical significance which persisted after adjusting for probable confounders (OR 1.8, 95% CI: 1.2-2.6) and (OR 1.9, 95% CI: 1.2-3.0) respectively. Young age and high levels of education had synergistic effect on the relationship between knowledge and birth preparedness. The associations between knowledge of at least one key danger sign during childbirth or knowledge that prolonged labour was a key danger sign and birth preparedness were not statistically significant. Conclusions The prevalence of recently delivered women who had knowledge of key danger signs or those who were birth prepared was very low. Since the majority of women attend antenatal care sessions, the quality and methods of delivery of antenatal care education require review so as to improve its effectiveness. Universal primary and secondary education programmes ought to be promoted so as to enhance the impact of knowledge of key danger signs on birth preparedness practices.